To Design A Semi-Auto Coconut Peeling Machine - Che Anuar, Muhammad Aliy Afiq; Abd Rahim, Abd Khalil (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The design of a semi-automatic coconut peeling machine was successfully produced and implemented with the assistance and guidance of George E. Dieter’s design technique. Throughout the design process, conclusions are drawn from the findings and presented to the client. Research and numerous start-ups culminated in developing a semi-automatic coconut peeling machine to peel coconuts, which met the project’s objectives in full. This design has been thoroughly researched to demonstrate that it can meet all of the product’s specifications. Based on theoretical calculations, it is projected that the daily production rate is 220 coconuts. Daily, the machine weighs an overall total of 186.932 kg and consumes an overall total of 40.149 watts. Following that, to achieve the project’s goal, the use of SolidWorks had been improved during the project’s development. The three basic mechanics employed in this machine’s construction are side peeling, top peeling, and bottom cutting. Each of these mechanisms works in concert with the others to make a more efficient machine design possible by coordinating their operations. Finally, this project can assist coconut-based Small and Medium-Sized Enterprises (SME) in their everyday operations by peeling the coconut following their selling requirements.